The Application Of Brainstorming To Improve Student’s Writing Skill - Ita Brasilia Nurhasanah; Ria Martin; Rizky Amalia (Bandar Lampung University, 2015)
Writing is one of the four basic language skills (reading, listening, writing, and speaking) that shoul be mastered by students. The aim of this research is to investigate the effect of brainstorming in improving student’s writing skill. The participants are students of English Study Program of Bandar Lampung University.The study shows that teaching writing by brainstorming method is successful. The students can develop their ideas in writing essay by using brainstorming technique because it helped them in organizing and arranging ideas into written text.